2018
DOI: 10.1007/s11764-018-0681-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effectiveness and cost-effectiveness of high versus low-to-moderate intensity resistance and endurance exercise interventions among cancer survivors

Abstract: PurposeThis study aimed to evaluate the long-term effectiveness and cost-effectiveness of high intensity (HI) versus low-to-moderate intensity (LMI) exercise on physical fitness, fatigue, and health-related quality of life (HRQoL) in cancer survivors.MethodsTwo hundred seventy-seven cancer survivors participated in the Resistance and Endurance exercise After ChemoTherapy (REACT) study and were randomized to 12 weeks of HI (n = 139) or LMI exercise (n = 138) that had similar exercise types, durations, and frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(81 citation statements)
references
References 38 publications
2
56
1
4
Order By: Relevance
“…Challenges to display beneficial effects of exercise training on cognitive and affective CRF has been evident in patients with breast cancer immediately following completion of chemotherapy [ 29 ]. Conversely, a trial conducted post-chemotherapy on breast cancer survivors assessing different exercise loads/intensities demonstrated that only the group performing high load resistance training combined with high-intensity continuous/interval training was able to counteract mental fatigue [ 30 ], and results from their 12-month follow-up study showed that the higher intensity group was superior to lower intensity exercise on role functioning [ 31 ]. It may be speculated that the HIIT component in the current trial may have played a role in inducing beneficial effects for cognitive CRF found for AT-HIIT, possibly through beneficial effects of HIIT on cerebral oxygenation [ 32 ] and/or improvements in information processing speed [ 33 ] as found in obese and elderly individuals, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Challenges to display beneficial effects of exercise training on cognitive and affective CRF has been evident in patients with breast cancer immediately following completion of chemotherapy [ 29 ]. Conversely, a trial conducted post-chemotherapy on breast cancer survivors assessing different exercise loads/intensities demonstrated that only the group performing high load resistance training combined with high-intensity continuous/interval training was able to counteract mental fatigue [ 30 ], and results from their 12-month follow-up study showed that the higher intensity group was superior to lower intensity exercise on role functioning [ 31 ]. It may be speculated that the HIIT component in the current trial may have played a role in inducing beneficial effects for cognitive CRF found for AT-HIIT, possibly through beneficial effects of HIIT on cerebral oxygenation [ 32 ] and/or improvements in information processing speed [ 33 ] as found in obese and elderly individuals, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, reports suggest that analyses including comprehensive costs, which capture reductions in health care utilization more consistently, favor resource‐intensive and exercise‐intensive programs. A randomized trial that compared high‐intensity and low‐intensity exercise programs found that the former were cost‐effective, mostly due to significantly lower health care costs in the high‐intensity exercise group . Several studies noted reductions in unplanned hospitalizations, lengths of stay, and emergency room visits among patients who participated in exercise programming .…”
Section: Implementation Issuesmentioning
confidence: 99%
“…Physical activity (PA) benefits people living with or beyond cancer by improving physical function and QoL during and after cancer treatment, and cancer-related outcomes like treatment completion, maintenance of, or faster return to, pretreatment health, fewer unnecessary healthcare visits and better survival rates [6,[17][18][19][20][21][22]. Improvements are greater in those engaging in PA sooner after a diagnosis [23].…”
Section: Introductionmentioning
confidence: 99%